2017
DOI: 10.1242/jcs.202879
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal motifs in promyelocytic leukemia protein isoforms critically regulate PML nuclear body formation

Abstract: Promyelocytic leukemia protein (PML) nuclear bodies (NBs), which are sub-nuclear protein structures, are involved in a variety of important cellular functions. PML-NBs are assembled by PML isoforms, and contact between small ubiquitin-like modifiers (SUMOs) with the SUMO interaction motif (SIM) are critically involved in this process. PML isoforms contain a common N-terminal region and a variable C-terminus. However, the contribution of the C-terminal regions to PML-NB formation remains poorly defined. Here, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 51 publications
5
33
0
Order By: Relevance
“…This is consistent with previous publications that have shown that SUMOylation of PML is necessary for PML to interact with other proteins and to form PML-NBs (54). Additional studies have also found that a SUMO-interacting motif (SIM) contained within the PML protein may be necessary for the interaction of PML with other SUMOylated proteins (55). While prediction software identified four possible SIMs in the R12 protein sequence, our analysis of immunoprecipitated R12-FLAG protein found that R12 protein was SUMO-1 modified ( Fig.…”
supporting
confidence: 92%
“…This is consistent with previous publications that have shown that SUMOylation of PML is necessary for PML to interact with other proteins and to form PML-NBs (54). Additional studies have also found that a SUMO-interacting motif (SIM) contained within the PML protein may be necessary for the interaction of PML with other SUMOylated proteins (55). While prediction software identified four possible SIMs in the R12 protein sequence, our analysis of immunoprecipitated R12-FLAG protein found that R12 protein was SUMO-1 modified ( Fig.…”
supporting
confidence: 92%
“…cDNA was synthesized using reverse transcriptase (Promega). Full length genes studied were inserted to the prk5-Flag, GFP or mCherry vectors [53]. The prk5-Flag vector was kindly provided by Dr. Jun Tang (China Agricultural University) and Flag was replaced by GFP or mCherry when necessary.…”
Section: Methodsmentioning
confidence: 99%
“…All PML isoforms share the same N‐terminal region that contains the Lys 160 (K160) residue that can be SUMOylated, and a variable C‐terminal segment. PML‐I contains a SUMO‐interacting motif (SIM) that can bind K160 forming a composite PDR . Different PML isoforms show differential regulation of this SUMO:SIM interaction: PML‐VI (lacking SIM, thus unable to phase‐separate), PML‐II (having an inhibitory MR that can shut down LLPS even with an intact SIM), PML‐III and PML‐V (both having a new PDR that can make them phase‐separate even if SIM is mutated), and PML‐IV (containing both an inhibitory MR and a new SUMO‐binding PDR).…”
Section: Phase Separation and Alternative Splicingmentioning
confidence: 99%
“…FUS ubiquitination has also been stated to be of importance; however, the role of this PTM is unclear . SUMOylation was already mentioned in conjunction with PML bodies .…”
Section: Post‐translational Modifications Turning Phase Separation Onmentioning
confidence: 99%